POPULATION OF THE UZBEK SSR ( 1926 , 1939 ) HELD UNION POPULATION LIST ACCORDING TO THE RESULTS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The primary source of information about the population is census documents. These documents provide systematic data on the population size and its distribution across the republic, urban and rural settlements, nationality, language, gender, age, marital status, social origin, literacy, and education levels. The article examines the results of the 1926 and 1939 censuses, highlighting the social status of the population in the Uzbek SSR and the policies implemented by the Bolsheviks regarding the population.